The Function of Flake Tools in Prehistoric Society of East Sabah: (Fungsi Alat Repih Masyarakat Prasejarah Timur Sabah) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2022)
Flake tools are flake of stones which were used as a tool for light work by prehistoric society. These flakes are obtained by flaking the core, a process of making a pebble tool. However, the flake which obtained from core indicate there is a specific method to produce the flake tools. This special method shows the society during that time already have the knowledge to produce flake tools. Flake tools which come from human striking can be distinguished from naturally crack fragment based on the characteristics such as the presence of bulb percussion, ripples and fissures. The artifacts of flake tools which were analysed are from the Paleolithic sites in the Tingkayu Valley for instance the Tingkayu Open Site, Madai Cave and Baturong Cave. These three sites are located on the East Coast of Sabah. Two of them are cave sites from limestone formations which are Baturong Cave and Madai Cave. While the Tingkayu site is an open site. The analysis of flake tools for these three sites is focusing on the function of flake tools whether they have the same function or not. Thus, through image analysis should be conducted to identify the function and value of the flake tools for different activities. The results of use wear analysis showed that the prehistoric society of Eastern Sabah in general using flake tools for drilling, slicing, scraping, grinding and multi functions uses. This study proves that the early society of Eastern Sabah were more economical in producing stone tools because they used flake tools for multifunction.